Rock mechanics. meeting society's challenges and demands : proceedings of the 1st Canada-US Rock Mechanics Symposium, Vancouver, Canada, 27-31 May 2007 /: meeting society's challenges and demands : proceedings of the 1st Canada-US Rock Mechanics Symposium, Vancouver, Canada, 27-31 May 2007. Fundamentals, new technologies & new ideas : Volume 1, (2007) - Unknown
No abstract available